Internasionalisasi Branding Desa Wisata Jatiluwih melalui Pelatihan Videografi bagi Mahasiswa Asing - Budiman, Diky; Gunarsa, I Ketut (Insan Kreasi Media, 2025)
Jatiluwih Village in Bali is one of the leading tourist destinations that has been designated as a World Cultural Heritage by UNESCO. However, digital promotion of this village is still not optimal, especially in reaching international markets. The main challenge lies in the limited local human resources in producing digital content that suits the preferences of foreign tourists. This community service activity aims to improve the quality of digital branding of Jatiluwih Village through videography training for foreign students from Xiamen Nanyang University, China. The method used is service learning, where students are directly involved in the process of producing promotional videos based on local culture. Activities were carried out in the form of training, field observations, interviews with the community, production of video content, and socialization of results. The results of the activity show that the participation of foreign students is able to produce promotional content that is culturally relevant and visually appealing. This service emphasizes the importance of international collaboration and educational approaches in supporting the promotion of community-based tourism in a sustainable and global manner.